Performance optimization of AlGaN-based LEDs by use of ultraviolet-transparent indium tin oxide: Effect of in situ contact treatment. (4th April 2018) - Tu, Wenbin; Chen, Zimin; Zhuo, Yi; Li, Zeqi; Ma, Xuejin; Wang, Gang
Abstract: Ultraviolet (UV)-transparent indium tin oxide (ITO) grown by metal–organic chemical vapor deposition (MOCVD) is used as the current-spreading layer for 368 nm AlGaN-based light-emitting diodes (LEDs). By performing in situ contact treatment on the LED/ITO interface, the morphology, resistivity, and contact resistance of electrodes become controllable. Resistivity of 2.64 × 10 −4 Ω cm and transmittance at 368 nm of 95.9% are realized for an ITO thin film grown with Sn-purge in situ treatment. Therefore, the high-power operating voltage decreases from 3.94 V (without treatment) to 3.83 V (with treatment). The improved performance is attributed to the lowering of the tunneling barrier at the LED/ITO interface.